Perspective of academics after the easing of mandatory mask use (Research, Society and Development, 2022)
Objective: To assess the perception of academics after the easing of mandatory mask use, as well as to identify the safety and insecurities that nursing students feel with this change, after a long period of use of the face mask in the prevention of contamination by the virus. of SARS-CoV-2. Methodology: This is a mixed methods study, carried out in a private institution in southern Brazil. For data collection, a sociodemographic questionnaire and a semi-structured questionnaire were applied to a target population of 50 nursing students. Data production took place through a semi-structured interview from July to August 2022. Data were entered into a spreadsheet in the Microsoft Office Excel 2019 program and analyzed using descriptive and inferential statistics. Results: There was a greater predominance of females with a mean age of 18 to 39 years, it was identified that most participants still do not feel comfortable circulating without the use of the mask. Conclusion: It was possible to conclude that despite the flexibilization of the use of masks in Brazil and in the world and even after the advancement of vaccinations, at this current moment of the pandemic, many academics are still afraid of returning to the streets and other spaces without the use of the mask. face mask. This is because the transmission of COVID-19 occurs mainly through the air and over short distances.